The alternative pathway is required, but not alone sufficient, for retinal pathology in mouse laser-induced choroidal neovascularization - Rohrer, Bärbel (2011)
Human genetic studies have demonstrated that polymorphisms in different complement proteins can increase the risk for developing AMD. There are three pathways of complement activation, classical (CP), alternative (AP), and lectin (LP), which all activate a final common pathway. Proteins encoded by the AMD risk genes participate in the AP (CFB), CP/LP (C2), or in the AP and final common pathway (C3). Here we tested which pathway is essential in mouse laser-induced CNV. CNV was analyzed using single complement pathway knockouts (i.e., eliminating one complement pathway at a time), followed by a double knockout in which only the AP is present, and the CP and LP are disabled, using molecular, histological and electrophysiological outcomes. First, single-gene knockouts were analyzed and compared to wild type mice; C1q(−/−) (no CP), MBL(−/−) (no LP), and CFB(−/−) (no AP). Six days after the laser-induced lesion, mice without a functional AP had reduced CNV progression (P<0.001) and preserved ERG amplitudes, whereas those without a functional CP or LP were indistinguishable from the wild type controls (P>0.3). Second, AP-only mice (C1q(−/−) MBL(−/−)) were as protected from developing CNV as the CFB(−/−) mice. The degree of pathology in each strain correlated with protein levels of the angiogenic and anti-angiogenic proteins VEGF and PEDF, respectively, as well as levels of terminal pathway activation product C5a, and C9. The analysis of complement activation pathways in mouse laser-induced CNV allows for the following conclusions. Comparing the single pathway knockouts with those having only a functional AP showed: (1) that AP activation is necessary, but not alone sufficient for injury; and (2) that initial complement activation proceeds via both the LP and CP. Thus, these data indicate an important role for the AP in the generation of complement-dependent injury in the RPE and choroid via amplification of CP- and LP-initiated complement activation. Improving our understanding of the local regulation of this pathway in the eye is essential for developing improved treatment approaches for AMD.